2014
DOI: 10.1186/1471-2458-14-766
|View full text |Cite
|
Sign up to set email alerts
|

Occupational injuries among children and adolescents in Cusco Province: a cross-sectional study

Abstract: BackgroundAlthough the number of child laborers in Latin America is generally high, data on occupational hazards and injuries is insufficient. The objective of this study was therefore to determine the lifetime prevalence of and risk factors for occupational injuries among working students (10–17 years old) in Cusco Province.MethodsA cross-sectional study was conducted at five public night schools. 375 students (response 91.5%) completed an interview-based questionnaire on socio-demographics, work-related fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 6 publications
2
11
1
3
Order By: Relevance
“…In these five studies, in summary, the major exposure of concern was social stress, typically as related to lower family SES, and the major outcome of concern was loss of education due to absence from school and/or some form of abuse [ 65 69 ]. In addition, Schlick et al covered nonagricultural, nonmining work and domestic work in Cusco Province of Peru [ 70 ]. In this study, physical hazards resulting in falls were the greatest reported concern [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these five studies, in summary, the major exposure of concern was social stress, typically as related to lower family SES, and the major outcome of concern was loss of education due to absence from school and/or some form of abuse [ 65 69 ]. In addition, Schlick et al covered nonagricultural, nonmining work and domestic work in Cusco Province of Peru [ 70 ]. In this study, physical hazards resulting in falls were the greatest reported concern [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Schlick et al covered nonagricultural, nonmining work and domestic work in Cusco Province of Peru [ 70 ]. In this study, physical hazards resulting in falls were the greatest reported concern [ 70 ]. It should also be noted how in two of these five studies gender showed varying results—there were differences reported by Naeem et al in Pakistan [ 67 ], where most girls—outnumbered compared to the boys 1 : 5 in the study sample—were reported to work as domestic servants or as pickers through garbage at dumpsites, but no statistically significant differences were reported by Shafiq in Bangladesh [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Em relação aos acidentes de trabalho e doenças decorrentes, 4 alunos dessa amostra referiram ter sofrido essas situações, problemática essa, bastante preocupante, principalmente quando se trata dessa faixa etária em que a repercussão de um AT pode modificar completamente sua trajetória social. De fato, um estudo realizado na Província de Cusco (Perú), com 375 alunos trabalhadores situados na faixa etária de 10 a 17 anos, 72% referiram já ter sofrido lesões leves (cortes e abrasões), 3% relataram ter-se envolvido em lesões graves (amputações, luxação e fraturas) 21 .…”
Section: Discussionunclassified
“…de las lesiones y enfermedades ocupacionales. A manera de ejemplificar lo anterior, un estudio en Cusco realizado en menores trabajadores mostró una prevalencia de lesiones graves del 3%, las cuales muchas veces ocurrieron bajo condiciones laborales deficientes (14) y, por otro lado, está la alta tasa de trabajo informal que aún fluctúa en más del 50% (15) .…”
Section: Referencias Bibliográficasunclassified